Synthesis and highly visible-induced photocatalytic activity of CNT-CdSe composite for methylene blue solution - Chen Ming-Liang; Oh Won-Chun (Nanoscale Research Letters, 2011)
Abstract Carbon nanotube-cadmium selenide (CNT-CdSe) composite was synthesized by a facile hydrothermal method derived from multi-walled carbon nanotubes as a stating material. The as-prepared products were characterized by X-ray diffraction, scanning electron microscopy with energy dispersive X-ray analysis, transmission electron microscopy (TEM), and UV-vis diffuse reflectance spectrophotometer. The as-synthesized CNT-CdSe composite efficiently catalyzed the photodegradation of methylene blue in aqueous solutions under visible-light irradiation, exhibiting higher photocatalytic activity.